Selektivitas Pancing Terhadap Hasil Tangkapan Ikan Selar (Selar crumenopthalmus) di Perairan Selat Seram - Haruna Haruna; Kedswin G. Hehanussa; Julian Tuhumury; Ninfint Tuankotta (Universitas Sam Ratulangi, 2023)
Gear selectivity is an important part of controlling the size of fish that are suitable for catching so that fish resources are maintained. The size of the hook is one of the factors that affect the selectivity of the fishing line. The purpose of this study is to analyze the selectivity of fishing lines on the results of catching Selar crumenopthalmus. Fish sampling was carried out by following a series of fishing operations by fishermen using hook sizes no. 17 and 18. The Holt method was used to analyze and calculate the selectivity of hook size operated by fishermen on the total length of the fish line. Size distribution of the total length of hook no. 17 in the middle-class size 16.5 cm – 22.5 cm and hook no. 18 in the middle-size class 16.5 cm – 20.5 cm. The distribution of length sizes on both hooks tends to be normally distributed and the proportion of large lengths is higher on hook no. 17. The 50% and optimal (100%) chance of being caught for hook size no. 17 is 18.3 and 20.1 cm, respectively. while the size of hook no. 18 is 167 cm and 18 cm. It is recommended to use hook size for trevally resources in the Seram Strait waters is hook no. 17.